2002
DOI: 10.1126/science.1066176
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Dynamics During Catalysis

Abstract: Internal protein dynamics are intimately connected to enzymatic catalysis. However, enzyme motions linked to substrate turnover remain largely unknown. We have studied dynamics of an enzyme during catalysis at atomic resolution using nuclear magnetic resonance relaxation methods. During catalytic action of the enzyme cyclophilin A, we detect conformational fluctuations of the active site that occur on a time scale of hundreds of microseconds. The rates of conformational dynamics of the enzyme strongly correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
735
3
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 688 publications
(768 citation statements)
references
References 31 publications
26
735
3
4
Order By: Relevance
“…7, A and C). These regions correlate well with the earlier-reported regions for peptide interaction and catalysis in human CypA (9,16). In this study, the maximal intensity change was observed for N120, and even at low equivalents of the peptide, considerable CSP was measured.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…7, A and C). These regions correlate well with the earlier-reported regions for peptide interaction and catalysis in human CypA (9,16). In this study, the maximal intensity change was observed for N120, and even at low equivalents of the peptide, considerable CSP was measured.…”
Section: Discussionsupporting
confidence: 91%
“…Eisenmesser and co-workers proposed that the cis conformer of the peptide interacts with residues A101, N102, A103, K82, and R55 of the enzyme; afterward, the enzyme catalyzes rotation of the peptide-prolyl bond by 180 to produce the trans conformation and makes contacts around residues L98 and S99. During isomerization, the C-terminus of the peptide bond is free to rotate, whereas the N-terminus of the bond remains bound at the catalytic site of the enzyme (9). The authors also concluded that R55 is the key player in cis-trans isomerization, which is supported by mutational studies (9,10).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Flexibilities and dynamics in protein conformation are essential for its function, playing key roles in molecular recognition, rate-limiting conformational transitions, and catalysis (Cole et al, 2002;Eisenmesser et al, 2002). The time scales of these protein conformational motions vary widely, from picoseconds to seconds, making solution NMR a suitable technique for analyzing such motions.…”
Section: Introductionmentioning
confidence: 99%